Three-dimensional lung parenchyma model for studies of Aspergillus fumigatus infection and antifungal treatment - Fortes, Bruna Nakanishi; Wirth, Fernanda; dos Santos, Aline Martins [UNESP]; Chorilli, Marlus [UNESP]; Freitas, Vanessa Morais; Farias, Jennifer; Chambergo, Felipe S; Nunes C Dantas, Viviane Abreu; Ishida, Kelly (Taylor & Francis, 2024)
Aim: This work aims to standardize the three-dimensional hydroxyethyl-alginate-gelatin (HAG) scaffold as a model to evaluate Aspergillus fumigatus biofilm and antifungal treatments. Methods: The scaffold was characterized by physical, rheological and microscopic analyses; the antibiofilm action was evaluated by determination of cfu and metabolic activity. Results: The scaffold was non-toxic showing stability in aqueous media, swelling capacity, elasticity and had homogeneously distributed pores averaging 190 μm. The A. fumigatus biofilm established itself very well on the scaffold and treatment with amphotericin B and voriconazole reduced viable cells and metabolic activity. Conclusion: The HAG scaffold proved to be a model to mimic lung parenchyma, suitable for establishing a 3D biofilm culture of A. fumigatus and evaluating the efficacy of antifungals.
Keywords: amphotericin B; antifungals; Aspergillus fumigatus; biofilm; lung epithelial cell; scaffold; three-dimensional cell culture; voriconazole